Losing the news : the future of the news that feeds democracy - Jones, Alex S.; Annenberg Foundation Trust at Sunnylands; Annenberg Public Policy Center (Oxford ; New York : Oxford University Press, 2009)
Pulitzer Prize-winning journalist Alex S. Jones explores how the epochal changes sweeping the media have eroded the core news that has been the essential food supply of our democracy. At a time of dazzling technological innovation, Jones says that what stands to be lost is the fact-based reporting that serves as a watchdog over government, holds the powerful accountable, and gives citizens what they need. In a tumultuous new media era, with cutthroat competition and panic over profits, the commitment of the traditional news media to serious news is fading. Should we lose a critical mass of this news, our democracy will weaken--and possibly even begin to fail. This book is also a call to arms. Despite the current crisis, there are many hopeful signs, and Jones closes by looking over the horizon and exploring ways the iron core can be preserved.--From publisher description.
The iron core -- Media and democracy -- The fragile First Amendment -- Objectivity's last stand -- Media ethics- the painful balance -- The curious story of news -- Newspapers on the brink -- The new news media -- Saving the news.
"The Annenberg Foundation Trust at Sunnylands, the Annenberg Public Policy Center of the University of Pennsylvania."
Includes index.
Jaatri
Keywords: Journalism -- Political aspects -- United States; Journalism -- Economic aspects -- United States; Journalism -- Objectivity -- United States; Journalistic ethics -- United States